Slowing Down with Stinging Nettle - Kinnunen, Veera; Martz, Francoise; Rantala, Outi (Palgrave Macmillan, 2023)
In ‘Slowing down with stinging nettle,’ Veera Kinnunen, Françoise Martz, and Outi Rantala seek to develop transdisciplinary knowing methods by gathering around stinging nettle. Due to the rich cultural and biological heritage inscribed in nettle, it provides a fruitful starting point for transdisciplinary theorising about human–plant relations from the local nettle that is simultaneously present around the world. The three authors—a sociologist, a tourism researcher, and a biologist—end up inviting two plant mentors to their conversations, enabling them to attend to situated nettle relations. The plant mentors’ rich situated expertise in utilising nettle enables the authors to pay attention to the material, symbolic, and temporal particularities embedded in making a living with nettle.